Cell-contact-dependent activation of CD4+ T cells by adhesion molecules on synovial fibroblasts. Issue 3 (4th May 2017) - Mori, Masato; Hashimoto, Motomu; Matsuo, Takashi; Fujii, Takao; Furu, Moritoshi; Ito, Hiromu; Yoshitomi, Hiroyuki; Hirose, Jun; Ito, Yoshinaga; Akizuki, Shuji; Nakashima, Ran; Imura, Yoshitaka; et al.
Abstract: Objective : To determine how cell–cell contact with synovial fibroblasts (SF) influence on the proliferation and cytokine production of CD4 +  T cells. Methods : Naïve CD4 +  T cells were cultured with SF from rheumatoid arthritis patients, stimulated by anti-CD3/28 antibody, and CD4 +  T cell proliferation and IFN-γ/IL-17 production were analyzed. To study the role of adhesion molecules, cell contact was blocked by transwell plate or anti-intracellular adhesion molecule-1 (ICAM-1)/vascular cell adhesion molecule-1(VCAM-1) antibody. To study the direct role of adhesion molecules for CD4 +  T cells, CD161 +  or CD161 - naïve CD4 +  T cells were stimulated on plastic plates coated by recombinant ICAM-1 or VCAM-1, and the source of IFN-γ/IL-17 were analyzed. Results : SF enhanced naïve CD4 +  T cell proliferation and IFN-γ/IL-17 production in cell-contact and in part ICAM-1-/VCAM-1-dependent manner. Plate-coated ICAM-1 and VCAM-1 enhanced naïve CD4 +  T cell proliferation and IFN-γ production, while VCAM-1 efficiently promoting IL-17 production. CD161 +  naïve T cells upregulating LFA-1 and VLA-4 were the major source of IFN-γ/IL-17 upon interaction with ICAM-1/VCAM-1. Conclusion : CD4 +  T cells rapidly expand and secrete IFN-γ/IL-17 upon cell-contact with SF via adhesion molecules. Interfering with ICAM-1-/VCAM-1 may be beneficial for inhibiting RA synovitis.